Torn apart: How the child welfare system destroys black families-and how abolition can build a safer world - Roberts, Dorothy (New York Basic books, 2022)
Many believe the child welfare system protects children from abuse. But as Torn Apart uncovers, this system is designed to punish Black families. Drawing on decades of research, legal scholar and sociologist Dorothy Roberts reveals that the child welfare system is better understood as a (3z(Bfamily policing system(3y (Bthat collaborates with law enforcement and prisons to oppress Black communities. s